EFL STUDENTS’ PERCEPTIONS OF TIKTOK FOR ENGLISH LANGUAGE LEARNING IN INDONESIA: A MIXED-METHODS STUDY OF GENDER AND YEAR OF STUDY DIFFERENCES - Mkar Intana Hikmah; Daflizar Daflizar (English Education Department at FKIP Nommensen University, 2026)
TikTok has increasingly used as an informal learning resource by EFL students. This study investigated EFL students’ perceptions of TikTok for English language learning and examined whether those perceptions differed by gender and years of study. A sequential explanatory mixed-methods design was employed. Quantitative data were collected from 71 undergraduate students using a questionnaire adapted from the Technology Acceptance Model (TAM), which measured perceived ease of use, perceived usefulness, attitude toward use, behavioral intention, and actual system use. Qualitative data were then obtained from four selected participants through semi-structured interviews. The findings showed generally positive perceptions of TikTok, especially in terms of accessibility, ease of use, and usefulness. No statistically significant differences were found by gender (U = 472.000, p = .177, r = .16) or years of study (H (2) = 2.135, p = .344, ε² = .002). Interview findings showed that students valued TikTok for its concise content and support for vocabulary, pronunciation, and speaking, although distraction remained a challenge. These findings suggest that TikTok can serve as a useful supplementary learning tool when used in guided and self-regulated ways. However, the findings are limited to a single institutional context and largely based on self-reported data.